2019
DOI: 10.3389/fphar.2019.01452
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes From Astrocyte Processes: Signaling to Neurons

Abstract: It is widely recognized that extracellular vesicles subserve non-classical signal transmission in the central nervous system. Here we assess if the astrocyte processes, that are recognized to play crucial roles in intercellular communication at the synapses and in neuron-astrocyte networks, could convey messages through extracellular vesicles. Our findings indicate, for the first time that freshly isolated astrocyte processes prepared from adult rat cerebral cortex, can indeed participate to signal transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 46 publications
(79 reference statements)
3
79
0
Order By: Relevance
“…A great amount of globin co-localizes with collagen fibers, suggesting that NGB can be released by breast cancer cells in vivo. This result, in line with evidence demonstrating the presence of NGB in astrocytes derived exosomes [ 11 ], in serum of animal models after ischemic-reperfusion insults [ 40 ], and in plasma of human patients with traumatic brain injury [ 41 ], indicates that the extracellular NGB release is a common feature of this globin.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…A great amount of globin co-localizes with collagen fibers, suggesting that NGB can be released by breast cancer cells in vivo. This result, in line with evidence demonstrating the presence of NGB in astrocytes derived exosomes [ 11 ], in serum of animal models after ischemic-reperfusion insults [ 40 ], and in plasma of human patients with traumatic brain injury [ 41 ], indicates that the extracellular NGB release is a common feature of this globin.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, during the last years, the idea that NGB localization may provide some clues about its function and that stimuli able to change NGB level/localization might also affect such function, has earned growing interest [ 8 , 33 , 36 , 37 , 38 ]. Other independent studies further complicate this scenario, indicating that NGB may be released from astrocytes [ 11 ] and exogenous NGB can exert cytoprotective functions in astroglial cells [ 12 ] and retinal neurons [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely recognized that extracellular vesicles constitute a fundamental signal transmission in the central nervous system. Venturini and coauthors recently demonstrated that astrocytes are able to convey messages and transfer neuroglobin through extracellular vesicles, which selectively target neurons [18]. However, it is widely recognized that different cell types can release micro-vesicles, which operate as mediator of the inter-cellular communication ensuring short-and long-range exchange of information [19,20].…”
Section: Discussionmentioning
confidence: 99%